2017
DOI: 10.1093/nar/gkx071
|View full text |Cite
|
Sign up to set email alerts
|

CNBP acts as a key transcriptional regulator of sustained expression of interleukin-6

Abstract: The transcription of inflammatory genes is an essential step in host defense activation. Here, we show that cellular nucleic acid-binding protein (CNBP) acts as a transcription regulator that is required for activating the innate immune response. We identified specific CNBP-binding motifs present in the promoter region of sustained inflammatory cytokines, thus, directly inducing the expression of target genes. In particular, lipopolysaccharide (LPS) induced cnbp expression through an NF-κB-dependent manner and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 66 publications
6
57
0
Order By: Relevance
“…Because EGF triggers PKC activation, we further explored whether PKC phosphorylated CNBP in response to EGF. As previously noted, in vitro kinase assay showed that PKC phosphorylated CNBP as well as the NF‐κB subunit p65 (Figure S2). To determine whether EGF‐stimulated PKC induced CNBP nuclear translocation, we measured the amount of CNBP in the cytosolic and nuclear fractions from TC‐1 cells stimulated with EGF after pretreatment with the PKC inhibitor BIM‐I.…”
Section: Resultssupporting
confidence: 79%
See 4 more Smart Citations
“…Because EGF triggers PKC activation, we further explored whether PKC phosphorylated CNBP in response to EGF. As previously noted, in vitro kinase assay showed that PKC phosphorylated CNBP as well as the NF‐κB subunit p65 (Figure S2). To determine whether EGF‐stimulated PKC induced CNBP nuclear translocation, we measured the amount of CNBP in the cytosolic and nuclear fractions from TC‐1 cells stimulated with EGF after pretreatment with the PKC inhibitor BIM‐I.…”
Section: Resultssupporting
confidence: 79%
“…We previously identified the specific CNBP‐binding motif sequence of CTGAAAAt(a), which is present in the promotors of its target inflammatory genes . Interestingly, the promoter regions of tumor‐related genes , such as mmp‐2 , kras , mmp‐14 , and e2f2 also contained a very similar motif alignment essential for CNBP binding (Figure A and Doc S2).…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations